SMART FACTORIES AND THE HUMAN-AI COLLABORATION PARADIGM: REDEFINING MANUFACTURING EXCELLENCE - Aman Jain , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The emergence of smart factories marks a transformative era in manufacturing, where human-AI collaboration redefines operational excellence. The integration of artificial intelligence with Manufacturing Execution Systems creates a synergistic environment where advanced technologies and human expertise complement each other. From predictive scheduling to quality control and adaptive process management, smart factories demonstrate the potential of human-AI partnerships in optimizing production processes. The implementation challenges are addressed through transparent decision-making protocols, comprehensive workforce adaptation strategies, and robust technical infrastructure. As manufacturing evolves towards more sophisticated AI integration, the focus extends beyond individual facility optimization to encompass cross-facility coordination, supply chain integration, and environmental sustainability, promising a future where human intelligence and artificial intelligence work in harmony to achieve unprecedented levels of manufacturing efficiency.